Historia del campus de la Universidad de Lima: el proyecto fundacional de Héctor Velarde y la planificación moderna en el Perú - Fabbri García, Martín (2013)
This article forms part of a research project entitled History of the Uni-versity of Lima’s campus, which was based on the foundational project, designed by the architect Héctor Velarde Bergmann in 1964 and built in 1965. The objective was to identify the urban characteristics of the campus as well as investigate the relationship between the first University of Lima project and the other important university campus projects in Lima: the University City of San Marcos of 1956 and the Pontifical Catholic University campus of 1967. The urban characteristics of each of these campuses is analysed as well the University of Lima’s.